Entre o trabalho e as aspirações à empregabilidade: interlocuções com estudantes universitários após o estágio em curso técnico - Kehler, Gabriel dos Santos (2013)
This work is linked to the Research Line II - School Practices and Public Policies, of the Post-Graduation Program on Education, and to Kairós - Research Group on Work, Education and Public Policies, both from Federal University of Santa Maria - UFSM / RS. It had the funding (scholarship) from ANPED/IPEA/2011 covenant. The research aimed at analyzing how students, currently enrolled in undergraduation courses, who took the course in Technical Agriculture in Integrated Mode (Group- 2011) at the Farroupilha Federal Institute - Júlio Castilhos/ RS campus -, describe the work done in time and space of their internship and if this would influence on their choices to the continuity of their education. For that, we started with the proposition that the internship is configured as pedagogical praxis therefore constituted as an initial insertion into the world of work, and should not be reduced to one-sidedness of the conditions of employability. From this perspective, the study was based on a theoretical and methodological dialectical analysis, understood as the possibility of critical approach of the phenomena, based on historical materialism. As a procedure, semi-structured interviews were conducted with eight students. For analysis and systematization of the data produced, we used principles of content analysis, based on Bardin (2011), from a dialectical understanding. As a result, it was confirmed the initial hypothesis that justified the choice of the field and the subjects to be investigated, as well as the problematic proposal was supported, in which five of the eight subjects confirmed that the internship of technical course was incisive in terms of its pedagogical character for their choices of progression for their education in higher level.